Language Learning Strategies Used by EFL Fluent Speakers: A Case in Indonesian Context - M. Ali Ghufron (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
This study reported what language learning strategies are used by EFL fluent speakers in EFL speaking class and to reveal the fluent speakers’ awareness of the benefits of the language learning strategies. This research was conducted on six students in EFL Speaking Class of English Education Department of IKIP PGRI Bojonegoro, Indonesia, who were categorized as EFL fluent speakers. The research belongs to a case study. The data for this research were taken from in-depth interviews, observation, filling up questionnaires, and document analysis. The results of this study show that 1) in EFL sepaking class, the 1st student used cognitive, compensation, and social strategies, the 2nd student used cognitive and affective strategies, the 3rd student used cognitive, meta-cognitive and social strategies, the 4th student used meta-cognitive and social strategies, the 5th student used cognitive and affective strategies, and the 6th student used meta-cognitive and social strategies. 2) The students are strongly aware of the learning strategies’ benefits to improve their English skills. From the findings, it can be concluded that learning strategies are very useful and helpful in learning English as a foreign language. Learning strategies also bring the students reach the good achievement in improving their speaking skill.